PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PASIEN PADA KLINIK PPK1 PT PETROKIMIA GRESIK - Susanto, Heru; Mufarokhah, Nur (Jurnal Ekonomi dan Kewirausahaan Kreatif, 2023)
This study aims to examine the effect of service quality and facilities to the patient satisfaction at the PPK1 clinic of PT Petrokimia Gresik. This study uses a quantitative approach with multiple regression analysis method. The population in this study is the average number of patient visits per month is 4331. Determination of the sample using the Slovin theory with a sample of 100 respondents. The sampling technique used to non-probability sampling. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used descriptive analysis and multiple linear regression analysis and classical assumption test. Data analysis using the IBM SPSS 27 programs. The results showed that there was a partial effect of service quality on patient satisfaction at PT Petrokima Gresik's PPK1 clinic with t test results tcount > ttable, namely 2,544 > 1,984 and a significant level of 0,013 < 0,05. Facilities have a partial effect on patient satisfaction at the PPK1 clinic of PT Petrokimia Gresik with the results of the t test being tcount > ttable, namely 3,412 > 1,984 and a significant level of 0,001 < 0,05. Service quality and facilities have a simultaneous effect on patient satisfaction at the PPK1 clinic of PT Petrokimia Gresik with the results of the F test being Fcount > Ftable, which is 29,126 > 3,09 and a significant level of 0,000 < 0,05. Keywords: Service Quality, Facilities, Patient Satisfaction